IMAM AL-GHAZALI'S THOUGHTS ON THE COMPETENCE OF PROFESSIONAL TEACHERS IN THE AYYUHAL WALAD BOOK - Muhadri Muhadri; Ali Imran Sinaga; Akmal Walad Ahkas (Universitas Dharmawangsa Medan, 2020)
The purpose of the study was to determine the competence of Professional Teachers according to Imam Al-Ghazali. The research method in this writing is literature-oriented, in terms of methodological science, the character of this research is commonly referred to as library research, what is meant by library research is a research oriented to extracting information from literature sources. From the understanding obtained from the author's analysis of the book Ayyuhal Walad by Imama Al - Ghozali about the determinants of student success in the context of Imam Al - Ghozali not only in the success of a teacher in transferring knowledge but how a teacher makes students closer to the creator. Because the educational context possessed by Imam Al-Ghozali is to humanize a complete human being or a complete human being, so in his view not everyone is able to do it except a teacher, Muhammad Rasulullah SAW. The teacher must have the ability to mobilize and nurture his students in accordance with the values noble and useful life values according to religious views